Uterine cervical mesonephric hyperplasia with focal cystic change masquerading clinicopathologically as lobular endocervical glandular hyperplasia to malignancy - Ken-ichi Mizutani; Sohsuke Yamada; Satoko Nakada; Nozomu Kurose; Akane Aikawa; Chizuru Futatsuya; Motona Kumagai; Akihiro Shioya; Hiroshi Minato; Takayuki Nojima (Elsevier, 2018)
Introduction: Although uterine cervical mesonephric hyperplasia (MH) arising from mesonephric remnants is a well-known but uncommon entity, it might pose a clinicopathological diagnostic challenge to distinguish from lobular endocervical glandular hyperplasia (LEGH) or adenocarcinoma, if MH rarely presents as a lobular and/or cystic mass with expansion of the cervical wall. However, few papers have described the detailed clinicopathological characteristics of MH compared to those benign to malignant lesions. Case presentation: An early forties Japanese female presented with a history of increased vaginal watery discharge. Multiple cystic lesions measuring less than 3 mm in diameter generated a high signal intensity on T2-weighted MRI, in the bilateral aspects of the variably enlarged uterine cervix. A gross examination of a hysterectomy specimen revealed bilateral small multicystic lesions, filled partly with secreted fluids, measuring approximately 25 × 7 × 5 mm, respectively, located in the superficial to relatively deep cervical wall. A microscopic examination showed that these lesions predominantly consisted of a lobular proliferation of small to medium-sized tubules and cysts containing occasionally periodic acid-Schiff-positive eosinophilic/pink secreted materials, lined by bland-looking cuboidal to flattened epithelium. Immunohistochemically, these lining cells were specifically positive for CD10 in a characteristic luminal staining pattern, whereas negative for MUC6, and had a low MIB-1 labeling index. We ultimately made a diagnosis of cervical MH, lobular type, with focal cystic change. Conclusion: We should be aware that, since gynecologists/pathologists might misinterpret MH as LEGH to malignancy, including the malignant counterpart of MH, a wide panel of immunohistochemical antibodies can be helpful supplemental tools.